Strategi Pengembangan Usahatani Manggis (Garcinia Mangostana L.) di Kecamatan Wanayasa Kabupaten Purwakarta - Wulan Safitri; Yusuf Muhyiddin; Luthfi Nur’azkiya (Peneliti.net, 2021)
Mangosteen is a fruit commodity with high export demand. Wanayasa District, Purwakarta Regency is one of the sub-districts that has the potential to develop mangosteen farming. The purpose of the research: to find out how the mangosteen fruit farming cultivation technique, to know the internal and external factors and to know the strategy of developing mangosteen farming to increase farmers' income. The method used is quantitative and qualitative. Primary data collection by observation, interviews and questionnaires. Secondary data were obtained from various literature sources and sources of information related to this research. Research respondents: mangosteen farmers and stakeholders. The sample of respondents was carried out by purposive sampling. The analysis technique used is the analysis of IFS, EFS, SWOT Matrix and QSPM Matrix. The results of the research: the mangosteen cultivation technique includes land management, planting, maintenance and harvesting. The results of the analysis show that internal factors that become strengths are factors that become major strengths, while weaknesses are limited capital. External factors that become opportunities are market opportunities for fresh fruit consumption are still wide open, while threats are climate change and erratic weather. SWOT matrix analysis obtained several alternative strategies. Based on the QSPM matrix, the strategic priority is obtained by